2005
DOI: 10.1126/science.1107783
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Ultrathin Aluminum Oxide Film on NiAl(110)

Abstract: The well-ordered aluminum oxide film formed by oxidation of the NiAl(110) surface is the most intensely studied metal surface oxide, but its structure was previously unknown. We determined the structure by extensive ab initio modeling and scanning tunneling microscopy experiments. Because the topmost aluminum atoms are pyramidally and tetrahedrally coordinated, the surface is different from all Al2O3 bulk phases. The film is a wide-gap insulator, although the overall stoichiometry of the film is not Al2O3 but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
375
2
3

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 356 publications
(403 citation statements)
references
References 21 publications
23
375
2
3
Order By: Relevance
“…It should be also emphasized that STM images of the thin oxide films very often cannot be interpreted straightforwardly and therefore other supporting information is necessary to prove a proposed structure model (see, for example, [9,12]). …”
Section: Scanning Tunneling Microscopy (Stm)mentioning
confidence: 99%
See 2 more Smart Citations
“…It should be also emphasized that STM images of the thin oxide films very often cannot be interpreted straightforwardly and therefore other supporting information is necessary to prove a proposed structure model (see, for example, [9,12]). …”
Section: Scanning Tunneling Microscopy (Stm)mentioning
confidence: 99%
“…Vibrational spectroscopy is a useful tool for characterization of thin oxide films (see examples in [3,6,9,12]). Schroeder et al [18] reported IRA spectra at the different stages of the SiO 2 /Mo(112) film preparation.…”
Section: Vibrational Spectroscopy: Experiments Vs Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…[31] and the structure of the ultra thin aluminum oxide film on NiAl(110) was reported by Kresse et al [32], who combined scanning tunneling microscopy and DFT. They found the stoichiometry and geometry of the aluminum oxide film to be different from the bulk oxide.…”
Section: Introductionmentioning
confidence: 99%
“…Its structure and properties have been the object of intense studies across the world. Finally, Scanning Tunneling Microscopy (STM) and Atomic Force Microscopy (AFM) (Simon et al 2008) images with atomic resolution have been published, and density functional calculations (Kresse et al 2005) have allowed us to understand the film at the atomic level including its defect structure, which turns out to be particularly relevant when it comes to anchoring of metal nanoparticles (Schmid et al 2006). Figure 7 shows atomic resolution of STM and AFM images together with the structural model as deduced from Density Functional Theory (DFT) calculations at areas of the film that do not contain defects.…”
Section: Model Studiesmentioning
confidence: 99%